United States : Financial Sector Assessment Program-Technical Note-Insurance Supervision and Regulation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This Technical Note (TN) is a targeted review of cross-cutting themes building on the detailed assessment of the Insurance Core Principles (ICPs) conducted in 2015. The targeted review was chosen, in part, due to the performance of the U.S. insurance regulatory system in the 2015 detailed assessment where it was assessed that the U.S. observed 8 ICPs, largely observed 13 ICPs and partly observed 5 ICPs. The analysis relied on a targeted self-assessment against a subset of ICPs covering valuation and solvency, risk management, conduct, winding-up, corporate governance and enforcement, and the objectives, powers and responsibility of supervisors. The choice of subjects covered in this review is based on those aspects most significant to financial stability and a follow-up on key recommendations from the 2015 detailed assessment. The focus of the analysis has been on the state-based system of regulation and supervision, reflecting the existing institutional setup.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet